Standardizing Propagation Techniques for Conservation of Inula racemosa Hook. f. in Kashmir Himalayas - Sultan, Asma; Sofi, P. A.; Masoodi, T. H.; Pala, Nazir A.; Peerzada, Ishtiyak Ahmed; Parrey Qurat Ul Ain Binte Syed, Aafaq A.; Rafeeq, Jauhar; Un Nisa, Mir Muskan (Indian Forester, 2024)
The present study was aimed to standardize propagation techniques for conservation of Inula racemosa Hook. f. in Kashmir Himalayas due to its critically endangered status apart from having high market demand. The experiment was conducted in the research field of Faculty of Forestry, Benhama Ganderbal, SKUAST-Kashmir using RBD and the plant material was treated with stratification and rooting hormones. Among the various stratification treatments, moist stratification of 75 days recorded highest germination (79.33%), survival (55.00%), seedling height (30.42 cm), total biomass of seedling (22.30 g/seedling), seedling quality index (1.22), seedling vigor index (24.13) as compared to control (0.01%). Maximum sprouting (95.00%), rooting (91.67%), plant height (201.93 cm), shoot-root ratio (1.26), total biomass of seedling (691.74), seedling quality index (24.09) were reported when rhizomes were treated with IBA@100ppm. The standardization techniques can be used for mass multiplication of this endangered plant to fulfill the market demand and shall provide livelihood to concerned inhabitants. The development of these procedures and techniques will also be helpful in sustainable utilization and conservation of the species apart from making it of commercial use.